Drug sensitization induced by prenatal methamphetamine exposure - Macúchová, E; Slamberová, R (Ceskoslovenska fysiologie, 2016)
Women, who abuse drugs during pregnancy, expose not just themselves but also their developing fetus to impairing effects, which can have potentially harmful and even long-term effects on the exposed children. For some years, methamphetamine (MA) has dominated the illicit drug market in the Czech Republic and Slovakia; additionally this drug is on the rise worldwide. It is one of the most accessible drugs, and in many cases the first choice drug for many drug-addicted pregnant women; in part due to its anorectic and stimulant effects. These women are rarely aware of the consequences of their behavior and their pregnancy is hardly ever a good enough reason for giving up drug use. These findings are supported by many experimental studies that show the damaging effects of maternal MA exposure on their offspring. There is growing evidence that exposure to MA in utero not only causes birth defects and delays in infant development, but also impairs the brain reward neural pathways of a developing offspring in such a way, that it could increase the predisposition for drug addiction later in life. Previously published animal studies have shown that offspring of mothers exposed to MA during pregnancy are more sensitive to MA when they encounter this drug later in adulthood. With respect to increased sensitivity, the term of sensitization has been introduced. It is defined as augmented psychomotor activity, which can be observed after drug re-administration following discontinuation of repeated drug exposure, and has been demonstrated to develop not only after repeated drug administration in adulthood, but also after chronic prenatal exposure. Results from our studies have shown that prenatal MA exposure can influence the sensitivity to the effects of some drugs, given as a challenge, in adulthood, specifically to those with a similar action mechanism. Our findings indicate that cross-sensitization between prenatal MA exposure and adult drug treatment cannot be simply termed as a general drug addiction, since it seems that the mechanism by which a drug impairs specific neurotransmitter systems plays an important role. The study findings show that although the offspring of MA-addicted mothers have altered sensitivity to certain drugs in adulthood, they do not display increased active drug-seeking behavior. Therefore, if we extrapolate the results to humans, it appears that there is a relatively little risk that a person, whose mother abused MA during pregnancy, will actively seek out drugs.
Keywords: methamfetamin; dospělí; Methamphetamine; Female; Adult; ženské pohlaví; Slovakia; lidé; těhotenství; zpožděný efekt prenatální expozice; poruchy spojené s užíváním amfetaminu; Amphetamine-Related Disorders; Czech Republic; Prenatal Exposure Delayed Effects; Česká republika; stimulanty centrálního nervového systému; Slovenská republika; Pregnancy; Central Nervous System Stimulants; Humans